2014
DOI: 10.1590/s1415-47572014000200005
|View full text |Cite
|
Sign up to set email alerts
|

[No Title Available]

Abstract: Here we propose a registration process for population genetic isolates, usually geographic clusters of genetic disorders, based on the systematic search of rumors, defined as any type of account regardless of its reliability. Systematically ascertained rumors are recorded, and validated through a progressive process of pre-established steps. This paper outlines the conceptual basis for this approach and presents the preliminary results from a rumor-based nationwide registry of genetically isolated populations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…S11 and S12 ), it is likely that there is an enrichment of rare genetic diseases unique to these groups. While this is a pattern observed worldwide and has been extensively documented in isolated Old World populations ( 65 ), the diseases that may increase in frequency as the product of these phenomena of isolation are likely to be population-specific and should be systematically documented and addressed by the Peruvian health system based on other Latin American experiences ( 72 ) and can add to the growing number of studies finding new insights into biology through analysis of isolated populations. Further, the finding that few ClinVar ( 67 ) variants are present in Native American ancestry populations also stresses that these populations are underrepresented in genome studies and demands more sequencing efforts.…”
Section: Discussionmentioning
confidence: 99%
“…S11 and S12 ), it is likely that there is an enrichment of rare genetic diseases unique to these groups. While this is a pattern observed worldwide and has been extensively documented in isolated Old World populations ( 65 ), the diseases that may increase in frequency as the product of these phenomena of isolation are likely to be population-specific and should be systematically documented and addressed by the Peruvian health system based on other Latin American experiences ( 72 ) and can add to the growing number of studies finding new insights into biology through analysis of isolated populations. Further, the finding that few ClinVar ( 67 ) variants are present in Native American ancestry populations also stresses that these populations are underrepresented in genome studies and demands more sequencing efforts.…”
Section: Discussionmentioning
confidence: 99%
“…• The study of genetically isolated populations with chronic endemic diseases of a genetic cause, in addition to molecular characterization, allows the determination of the origin of the conglomerate, contributing to the reconstruction of the history of the population, but must also contribute to the evaluation of the needs of prevention and health and psychosocial care (Castilla & Schuler-faccini, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, we have notified local health authorities and the national epidemiological surveillance system about the situation and have been proposing alternatives of intervention with a comprehensive approach that includes multidisciplinary care and an approach to the psychosocial problems that affect this population. Work is underway to set up a reference center for managing FXS at the Hospital Universitario del Valle, with exceptional care for Ricaurte's patients. The study of genetically isolated populations with chronic endemic diseases of a genetic cause, in addition to molecular characterization, allows the determination of the origin of the conglomerate, contributing to the reconstruction of the history of the population, but must also contribute to the evaluation of the needs of prevention and health and psychosocial care (Castilla & Schuler‐faccini, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Their results show that Brazil has one cluster of high consanguinity rates (1.59%) in the Southeast region of the country; and two clusters of medium consanguinity rates (0.76 and 1.22%) in the Northeast and South regions, respectively [34]. Another study reported finding several genetic isolates in different cities across the Southeast region, such as spinocerebellar ataxia type 1 in São Paulo and spinocerebellar ataxia type 3 in Rio de Janeiro [35]. These data corroborate the findings of the present study, in which the highest IEM-related infant mortality rates during the period of analysis were reported in the South and Southeast regions.…”
Section: Discussionmentioning
confidence: 99%